Hydrogen sulfide and carnosine: modulation of oxidative stress and inflammation in kidney and brain axis - Calabrese, Vittorio; Scuto, Maria; Salinaro, Angela Trovato; Dionisio, Giuseppe; Modafferi, Sergio; Ontario, Maria Laura; Greco, Valentina; Sciuto, Sebastiano; Schmitt, Claus P.; Calabrese, Edward J.; Peters, Verena (Antioxidants, 2020)
Emerging evidence indicates that the dysregulation of cellular redox homeostasis and chronic inflammatory processes are implicated in the pathogenesis of kidney and brain disorders. In this light, endogenous dipeptide carnosine (β-alanyl-L-histidine) and hydrogen sulfide (H2S) exert cytoprotective actions through the modulation of redox-dependent resilience pathways during oxidative stress and inflammation. Several recent studies have elucidated a functional crosstalk occurring between kidney and the brain. The pathophysiological link of this crosstalk is represented by oxidative stress and inflammatory processes which contribute to the high prevalence of neuropsychiatric disorders, cognitive impairment, and dementia during the natural history of chronic kidney disease. Herein, we provide an overview of the main pathophysiological mechanisms related to high levels of pro-inflammatory cytokines, including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and neurotoxins, which play a critical role in the kidney-brain crosstalk. The present paper also explores the respective role of H2S and carnosine in the modulation of oxidative stress and inflammation in the kidney-brain axis. It suggests that these activities are likely mediated, at least in part, via hormetic processes, involving Nrf2 (Nuclear factor-like 2), Hsp 70 (heat shock protein 70), SIRT-1 (Sirtuin-1), Trx (Thioredoxin), and the glutathione system. Metabolic interactions at the kidney and brain axis level operate in controlling and reducing oxidant-induced inflammatory damage and therefore, can be a promising potential therapeutic target to reduce the severity of renal and brain injuries in humans.